Dos "nuevos" dibujos del maestro real Gaspar de Vega: el primer plano del Alcázar de Madrid, atribuido a Alonso Covarrubias, y el plano de la casa de servicios del Palacio de El Pardo - Herranz, Juan (Anuario del Departamento de Historia y Teoría del Arte, 1998)
The new attribution of the plan of the Alcázar of Madrid and the plan of La Casa de Servicios of El Pardo given to the royal master builder Gaspar de Vega, with other pieces of information will permit us to look through and to examine some significant aspects of these buildings of the XVIth century.